A Dirichlet problem of type p(x) - Kirchhoff via Fredholm alternative - Barahona Martínez, Willy David (2021)
The objective of this work is to obtain weak solutions for a type of problem of type p(x) - Kirchhoff. The result is obtained by Fredholm-type results for a pair of non-linear operators. In addition, the uniqueness of weak solutions is considered.